2022
DOI: 10.1111/1365-2435.14023
|View full text |Cite
|
Sign up to set email alerts
|

The ecological function of insect egg micropyles

Abstract: Insect egg micropyles are openings through the chorion allowing sperm entry for fertilisation. Micropyles are diverse structures showing remarkable variation in number, spatial arrangement and physical structure across extant insect orders. Despite being almost ubiquitous across insects, they have received little attention. As key morphological features of an immobile life stage, it is plausible that part of the diversity exhibited by micropyles is adaptive, supporting other egg structures during embryo develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 80 publications
(102 reference statements)
1
6
0
Order By: Relevance
“…Differences in the permeability of insect eggs is mostly determined by the structure of the eggshell and epidermis. As the rst protective layer for communication with the environment, the eggshell during the embryonic period has important physiological functions, such as protecting the embryo, maintaining gas exchange, preventing water loss, preventing pathogens from entering, and assisting sperm to enter the egg [29][30][31] . The current results showed that eggshells can reduce penetration by insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the permeability of insect eggs is mostly determined by the structure of the eggshell and epidermis. As the rst protective layer for communication with the environment, the eggshell during the embryonic period has important physiological functions, such as protecting the embryo, maintaining gas exchange, preventing water loss, preventing pathogens from entering, and assisting sperm to enter the egg [29][30][31] . The current results showed that eggshells can reduce penetration by insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…We first combined published datasets of sperm length (SpermTree: [38]), insect egg sizes [40] and the number of insect micropyles [39]. As yet, no study has brought together data on micropyle width.…”
Section: Methodsmentioning
confidence: 99%
“…As yet, no study has brought together data on micropyle width. We added to the data of Iossa [39], using published scanning electron microscope (SEM) micrographs to measure the external diameter of the micropyle external pore of insect species [41] contained within SpermTree (figure 1 a,b ). Some species of insect have heteromorphic sperm (two or more sperm types), e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reforestation can reduce the accumulation of combustible materials by increasing vegetation coverage and biodiversity, and then slow down the spread of fire. The selection of specific fireresistant tree species can form a natural fire barrier, improve soil structure, improve water retention capacity, and thus reduce fire risk (Iossa, 2022). In this study, BPNN algorithm is adopted.…”
Section: Evaluation Model Of the Impact Of Natural Materials Renewal ...mentioning
confidence: 99%